2012
DOI: 10.1016/j.yexcr.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin1 administration increases axonal elongation in dissociated primary sensory neuron cultures

Abstract: Neuregulin1 is a family of growth and differentiation factors involved in various functions of both peripheral and central nervous system including the regenerative processes that underlie regeneration of damaged peripheral nerves. In the present study we tested in vitro the effect of Neuregulin1 administration on dissociated rat dorsal root ganglion (DRG). Activity of neuregulin1 was compared to the activity of nerve growth factor in the same in vitro experimental model. Results showed that neurite outgrowth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…The length of the longest neurite was greater in SM compared with CM. Heregulin in SM might enhance the neurite outgrowth of NSC34 cells [26]. Among the other factors that are present in SM, bFGF is also known to enhance neurite outgrowth by stimulating the MEK-ERK1/2 and PI3K-AKT pathways [27].…”
Section: Resultsmentioning
confidence: 99%
“…The length of the longest neurite was greater in SM compared with CM. Heregulin in SM might enhance the neurite outgrowth of NSC34 cells [26]. Among the other factors that are present in SM, bFGF is also known to enhance neurite outgrowth by stimulating the MEK-ERK1/2 and PI3K-AKT pathways [27].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that neurotrophic factors provide neural survival following damage and that there is a direct association between exogenous neurotrophic factor application and axonal regeneration (22,49). In the evaluation of peripheral nerve regeneration, total number of axons in the distal part of nerve and functional tests are used (50)(51)(52).…”
Section: Regenerative Events Following Damagementioning
confidence: 99%
“…Similar results have been described for PNS cell cultures when DRG cells were grown on biomimetic scaffolds, although in this case, the maximal average neurite length described was 230 ± 30 μm. 10 Considering that DRG cells have been widely used as a model for in vitro nerve regeneration, because of their ability to produce axonal elongation compared to CNS cells, 49 the neurite lengths observed when CNS cortical neurons were grown on SFS fibers confirmed the optimal characteristics of these fibers to be used as scaffolds for nerve regeneration applications.…”
Section: Discussionmentioning
confidence: 95%